2020
DOI: 10.1016/j.virusres.2020.198005
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with respiratory pathogens among COVID-2019 cases

Abstract: Accumulating evidence shows that microbial co-infection increases the risk of disease severity in humans. There have been few studies about SARS-CoV-2 co-infection with other pathogens. In this retrospective study, 257 laboratory-confirmed COVID-19 patients in Jiangsu Province were enrolled from January 22 to February 2, 2020. They were reconfirmed by real-time RT-PCR and tested for 39 respiratory pathogens. In total, 24 respiratory pathogens were found among the patients, and 242 (94.2 %) patients were co-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
562
10
31

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(629 citation statements)
references
References 9 publications
26
562
10
31
Order By: Relevance
“…Our patients were sicker than in a study of hospitalised but not intubated patients and there was longer patient follow up [22]. Microorganisms recovered in our study were similar in some regards to published data [22] but with relatively few Streptococcus pneumoniae, Haemophilus, and Moraxella isolates compared with a Chinese study [25]. Testing was not done for Mycoplasma pneumoniae which was a common superinfecting pathogen in one review [26].…”
Section: Discussionsupporting
confidence: 74%
“…Our patients were sicker than in a study of hospitalised but not intubated patients and there was longer patient follow up [22]. Microorganisms recovered in our study were similar in some regards to published data [22] but with relatively few Streptococcus pneumoniae, Haemophilus, and Moraxella isolates compared with a Chinese study [25]. Testing was not done for Mycoplasma pneumoniae which was a common superinfecting pathogen in one review [26].…”
Section: Discussionsupporting
confidence: 74%
“…In ammatory storms have been mentioned in many studies, and our study also con rmed the in ammatory response [24] . This study indicated that male patients had higher levels of in ammatory markers (including CRP, SAA, FIB), suggesting that bacterial infection is more common in male patients and might aggravate the disease progression [25,26] . The elevated AST and CK levels suggested that it may be related to the tissue damage mediated by virus, and the male response is more severe than female.…”
Section: Discussionmentioning
confidence: 74%
“…Similar results were published recently [1 -4], showing in general low rates of bacterial and fungal co-infections and a widespread antibiotic use in patients with con rmed COVID-19. In one study only, a high incidence of bacterial and fungal coinfections was presented [5].…”
Section: Discussionmentioning
confidence: 95%